Палеоботанічні дослідження Трипільської культури - Янушевич, З.В.; Кременецький, К.В.; Пашкевич, Г.О. (Археологія, 1993)
Стаття узагальнює і підсумовує наслідки споровопилкових та палєоетноботанічних досліджень матеріалів Трипільської культури в межах всього ареалу. На підставі палеоетноботанічних даних подано реконструкцію асортименту вирощуваних рослин протягом трьох етапів існування Трипільської культури. На основании спорово-пыльцевых исследований отложений из разрезов ряда памятников установлено, что трипольские племена существовали в благоприятных природных условиях лесостепного ландшафта. Ассортимент выращивавшихся растений, установленный на основе палеоэтноботанических исследований материалов почти 100 трипольских памятников, выявляет большое сходство на протяжении трех последовательных этапов развития трипольской культуры. Его образовывали три пленчатые пшеницы — Triticum monococcum, Triticum dicoccon, Triticum spelta ; ячмень голозерный Hordeum vulgare var.coeleste и реже — ячмень пленчатый Hordeum vulgare, а также бобовые — горох посевной Pisum sativum и вика эрвилия Vicia ervilia. Пшеницы одно-зернянка Triticum monococcum и двузернянка Triticum dicoccon были распространены повсеместно с преобладанием того или иного вида на разных поселениях. Просо Panicum miliaceum вероятно, имело небольшое значение. Воз-растание его роли замечено только на этапе позднего Триполья в материалах памятников, расположенных на границе степной зоны, население которых имело контакты со скотоводами. Земледелие трипольских племен имело специфический состав выращивавшихся культур, хорошо приспособленных к примитивному способу обработки почвы и собранного урожая. On the base of the cryptogamous-pollen researches of the deposits from the sections of a number of the memorials it is considered that the Tripolian tribes lived under the favourable natural conditions of the forest-steppe landscape. The assortment of the cultivated plants determinated by the palaeoefhnobotanic researches of the materials from near 100
Tripolian memorials displays the great resemblance during the three consecutive stage of the development of Tripolskaja culture. It consists of a three sorts of the hulled wheat — Triticum monococcum, Tritucum dicoccon, Triticum spelta; the naked barley Hordeum vulgare var. coeleste and more rare the hulled barley Hordeum vulgare and the leguminous plants: the sowing pea Pisum sativum and the vetch Visia ervilia. The wheat Triticum monococcum and Tritucum dicoccon were spreaded everywhere, one or another sort of which prevailed on the different settlements. The millet Panicum miliaceum probably was of a little importance. The age roles of it were noticed only on the stage of Late Tripolie in the materials of memorials disposed at the boundary of the plain zone which population had the contacts with the herdsmen. The agriculture of Tripolian tribes had the specific set of the grown cultures which were well adopted to the primitive methods of the cultivation of land and gathering in the harvest.